A BEME systematic review of UK undergraduate medical education in the general practice setting: BEME Guide No. 32. (July 2015) - Park, Sophie; Khan, Nada F.; Hampshire, Mandy; Knox, Richard; Malpass, Alice; Thomas, James; Anagnostelis, Betsy; Newman, Mark; Bower, Peter; Rosenthal, Joe; Murray, Elizabeth; Iliffe, Steve; et al.
Abstract Background: General practice is increasingly used as a learning environment in undergraduate medical education in the UK. Aim: The aim of this project was to identify, summarise and synthesise research about undergraduate medical education in general practice in the UK. Methods: We systematically identified studies of undergraduate medical education within a general practice setting in the UK from 1990 onwards. All papers were summarised in a descriptive report and categorised into two in-depth syntheses: a quantitative and a qualitative in-depth review. Results: 169 papers were identified, representing research from 26 UK medical schools. The in-depth review of quantitative papers (n = 7) showed that medical students learned clinical skills as well or better in general practice settings. Students receive more teaching, and clerk and examine more patients in the general practice setting than in hospital. Patient satisfaction and enablement are similar whether a student is present or not in a consultation, however, patients experience lower relational empathy. Two main thematic groups emerged from the qualitative in-depth review (n = 10): the interpersonal interactions within the teaching consultation and the socio-cultural spaces of learning which shape these interactions. The GP has a role as a broker of the interactions between patients and students. General practice is a socio-cultural and developmental learning space for students, who need to negotiate the competing cultures between hospital and general practice. Lastly, patients are transient members of the learning community, and their role requires careful facilitation. Conclusions: General practice is as good, if not better, than hospital delivery of teaching of clinical skills. Our meta-ethnography has produced rich understandings of the complex relationships shaping possibilities for student and patient active participation in learning.